Nivolumab versus standard, single-agent therapy of investigator's choice in recurrent or metastatic squamous cell carcinoma of the head and neck (CheckMate 141): health-related quality-of-life results from a randomised, phase 3 trial. Issue 8 (August 2017) - Harrington, Kevin J; Ferris, Robert L; Blumenschein, George; Colevas, A Dimitrios; Fayette, Jérôme; Licitra, Lisa; Kasper, Stefan; Even, Caroline; Vokes, Everett E; Worden, Francis; Saba, Nabil F; Kiyota, Naomi; et al.
Summary: Background: Patients with platinum-refractory recurrent or metastatic squamous cell carcinoma of the head and neck have few treatment options and poor prognosis. Nivolumab significantly improved survival of this patient population when compared with standard single-agent therapy of investigator's choice in Checkmate 141; here we report the effect of nivolumab on patient-reported outcomes (PROs). Methods: CheckMate 141 was a randomised, open-label, phase 3 trial in patients with recurrent or metastatic squamous cell carcinoma of the head and neck who progressed within 6 months after platinum-based chemotherapy. Patients were randomly assigned (2:1) to nivolumab 3 mg/kg every 2 weeks (n=240) or investigator's choice (n=121) of methotrexate (40–60 mg/m 2 of body surface area), docetaxel (30–40 mg/m 2 ), or cetuximab (250 mg/m 2 after a loading dose of 400 mg/m 2 ) until disease progression, intolerable toxicity, or withdrawal of consent. On Jan 26, 2016, the independent data monitoring committee reviewed the data at the planned interim analysis and declared overall survival superiority for nivolumab over investigator's choice therapy (primary endpoint; described previously). The protocol was amended to allow patients in the investigator's choice group to cross over to nivolumab. All patients not on active therapy are being followed for survival. As an exploratory endpoint, PROs were assessed at baseline, week 9, and every 6 weeks thereafter using the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire–Core 30 (QLQ-C30), the EORTC head and neck cancer-specific module (EORTC QLQ-H&N35), and the three-level European Quality of Life–5 Dimensions (EQ-5D) questionnaire. Differences within and between treatment groups in PROs were analysed by ANCOVA among patients with baseline and at least one other assessment. All randomised patients were included in the time to clinically meaningful deterioration analyses. Median time to clinically meaningful deterioration was analysed by Kaplan-Meier methods. CheckMate 141 was registered with ClinicalTrials.org, number NCT02105636 . Findings: Patients were enrolled between May 29, 2014, and July 31, 2015, and subsequently 361 patients were randomly assigned to receive nivolumab (n=240) or investigator's choice (n=121). Among them, 129 patients (93 in the nivolumab group and 36 in the investigator's choice group) completed any of the PRO questionnaires at baseline and at least one other assessment. Treatment with nivolumab resulted in adjusted mean changes from baseline to week 15 ranging from −2·1 to 5·4 across functional and symptom domains measured by the EORTC QLQ-C30, with no domains indicating clinically meaningful deterioration. By contrast, eight (53%) of the 15 domains in the investigator's choice group showed clinically meaningful deterioration (10 points or more) at week 15 (change from baseline range, −24·5 to 2·4). Similarly, on the EORTC QLQ-H&N35, clinically meaningful worsening at week 15 was seen in no domains in the nivolumab group and eight (44%) of 18 domains in the investigator's choice group. Patients in the nivolumab group had a clinically meaningful improvement (according to a difference of 7 points or greater) in adjusted mean change from baseline to week 15 on the EQ-5D visual analogue scale, in contrast to a clinically meaningful deterioration in the investigator's choice group (7·3 vs −7·8). Differences between groups were significant and clinically meaningful at weeks 9 and 15 in favour of nivolumab for role functioning, social functioning, fatigue, dyspnoea, and appetite loss on the EORTC QLQ-C30 and pain and sensory problems on the EORTC QLQ-H&N35. Median time to deterioration was significantly longer with nivolumab versus investigator's choice for 13 (37%) of 35 domains assessed across the three questionnaires. Interpretation: In this exploratory analysis of CheckMate 141, nivolumab stabilised symptoms and functioning from baseline to weeks 9 and 15, whereas investigator's choice led to clinically meaningful deterioration. Nivolumab delayed time to deterioration of patient-reported quality-of-life outcomes compared with single-agent therapy of investigator's choice in patients with platinum-refractory recurrent or metastatic squamous cell carcinoma of the head and neck. In view of the major unmet need in this population and the importance of maintaining or improving quality of life for patients with recurrent or metastatic squamous cell carcinoma of the head and neck, these data support nivolumab as a new standard-of-care option in this setting. Funding: Bristol-Myers Squibb.